1997
DOI: 10.1002/bbpc.199700040
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sodium Colloids in Heavily Irradiated NaCl Crystals by Nuclear Magnetic Resonance

Abstract: Strong irradiation of NaCl crystals results in a formation of sodium colloids which exhibit metallic properties. In consequence, besides the 23 Na line of NaCl a second well-separated 23 Na line occurs in the NMR spectrum caused by the Knight shift of the conduction electrons. We present Knight shift and nuclear spin relaxation mea surements performed on the "metallic" 23 Na line in e "-irradiated NaCl single-crystals between about 4 and 390 K. Evaluation of the data leads to detailed information on the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…It is important to note here that the sizes of the radiation-induced Na and Cl 2 precipitates, obtained by means of the high-resolution x-ray diffraction experiments, are much larger than those estimated from earlier investigations with other techniques [1][2][3][4][5][6][7][8][9][10][11]. In contrast with the 'x-ray sizes' in the range of several hundred angstroms, presented in tables 1 and 2, the results obtained with the other techniques suggest that the average size of the precipitates is a few dozen angstroms, which means that there is a discrepancy of at least one order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note here that the sizes of the radiation-induced Na and Cl 2 precipitates, obtained by means of the high-resolution x-ray diffraction experiments, are much larger than those estimated from earlier investigations with other techniques [1][2][3][4][5][6][7][8][9][10][11]. In contrast with the 'x-ray sizes' in the range of several hundred angstroms, presented in tables 1 and 2, the results obtained with the other techniques suggest that the average size of the precipitates is a few dozen angstroms, which means that there is a discrepancy of at least one order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…differential scanning calorimetry (DSC), electron paramagnetic resonance (EPR), AC conductivity, nuclear magnetic resonance (NMR), optical absorption spectroscopy, Raman scattering, and atomic force microscopy) has shown that during exposure of NaCl to ionizing radiation at elevated temperatures (e.g. 100 • C), with increasing dose increasing amounts of metallic Na and chlorine bubbles are formed [1][2][3][4][5][6][7][8][9][10][11]. Until now the physical properties of the metallic Na precipitates have been studied most extensively, and these investigations have shown that quite often the Na nanoparticles behave anomalously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic and magnetic properties of these crystals are similar to those of quasi-onedimensional conducting and polymeric compound RbC 60 (see [5,6]). Indeed, NMR spin relaxation [3,4,7], conduction electron spin resonance (CESR) and differential scanning calorimetry (DSC) [2,8] all suggest that NaCl-X is an electrical conductor above 160 K. However, between 160 and 40 K a gradual decrease of the CESR susceptibility with decreasing temperature has been observed. This was interpreted as evidence for the transition of NaCl-K to a non-conductive charge-density-wave (CDW) state [3] and indicative of small antiferromagnetic (AF) spin fluctuations persisting in heavily irradiated NaCl-KBF 4 crystals up to 160 K [2].…”
Section: Introductionmentioning
confidence: 97%